2015
DOI: 10.5812/ircmj.17(5)2015.28343
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Serum Hepcidin and Ferritin Levels in Patients With Thalassemia Major and Intermedia in Southern Iran

Abstract: Background:Hepcidin is a key regulator of iron absorption in humans. It is mainly affected by hypoxia and iron stores.Objectives:The current study aimed to determine the correlation between serum hepcidin and ferritin levels in patients with Thalassemia Major (TM) and Thalassemia Intermedia (TI).Patients and Methods:The current cross-sectional study investigated 88 randomly selected patients with Thalassemia, 48 TM and 40 TI, registered at the Thalassemia Clinic of Shiraz University of Medical Sciences, a refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
15
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
13
15
1
1
Order By: Relevance
“…However, we did not observe any significant difference between b-TM and b-TI patients as reported by others previously (19). This discrepancy may be due to the significant difference in age between the b-TM and b-TI groups and/or the clinical severity of irregularly chelated b-TI patients, and likely also due to the small number of studied patients.…”
Section: Discussioncontrasting
confidence: 82%
“…However, we did not observe any significant difference between b-TM and b-TI patients as reported by others previously (19). This discrepancy may be due to the significant difference in age between the b-TM and b-TI groups and/or the clinical severity of irregularly chelated b-TI patients, and likely also due to the small number of studied patients.…”
Section: Discussioncontrasting
confidence: 82%
“…We found that serum ferritin, the primary storage molecule for cellular iron, positively correlated with hepcidin in our CKD patients as previously documented among patients with CKD and those on dialysis (24,27,(31)(32)(33). This nding is also consistent with studies in non-CKD populations (34)(35)(36). In the setting of CKD, the direct relationship of hepcidin with ferritin may represent a protective effect of hepcidin against systemic iron overload (25).…”
Section: Discussionsupporting
confidence: 91%
“…9 The increased level of serum ferritin level was statistically highly significant as compared to that of normal healthy children (control group) as evident by pvalue which is less than 0.0001 (p<0.0001). The results of present series of study resembles with findings of Haghpanah S et al 10 Given the high prevalence of vitamin D deficiency in the general population and the added burden of increased metabolic demands, chronic medical care, and iron overload, it is not surprising that vitamin D deficiency is quite common in thalassemia major patients. The results of mean serum vitamin D were in close collaboration with the results obtained by Wood JC et al…”
Section: Discussionsupporting
confidence: 89%